2005
DOI: 10.1111/j.1525-1497.2005.40099.x
|View full text |Cite
|
Sign up to set email alerts
|

General medical and pharmacy claims expenditures in users of behavioral health services

Abstract: OBJECTIVE:To quantify the magnitude of general medical and/or pharmacy claims expenditures for individuals who use behavioral health services and to assess future claims when behavioral service use persists. MEASUREMENTS: Claims expenditures for behavioral health services, general medical services, and prescription medications. MAIN RESULTS:Just over one tenth of enrollees (10.7%) in 2001 had at least 1 behavioral health claim and accounted for 21.4% of total general medical, behavioral health, and pharmacy cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…People with a diagnosis of depression have about twice the health care costs that people without the diagnosis have (Kathol et al, 2005;Simon, VonKorff, & Barlow, 2003). Randomized controlled trials have shown significant improvement in clinical effectiveness and cost-effectiveness of collaborative models when care managers are used over usual primary care (Lave, Frank, Schulberg, & Kamlet, 1998;Pyne et al, 2003;Schoenbaum et al, 2001;Simon et al, 2001).…”
Section: Core Findings From the Evidencementioning
confidence: 99%
“…People with a diagnosis of depression have about twice the health care costs that people without the diagnosis have (Kathol et al, 2005;Simon, VonKorff, & Barlow, 2003). Randomized controlled trials have shown significant improvement in clinical effectiveness and cost-effectiveness of collaborative models when care managers are used over usual primary care (Lave, Frank, Schulberg, & Kamlet, 1998;Pyne et al, 2003;Schoenbaum et al, 2001;Simon et al, 2001).…”
Section: Core Findings From the Evidencementioning
confidence: 99%
“…• Nonresolution of mental health problems in medical patients is associated with medical illness nonresponse, nonadherence, higher medical illness complications, and increased death rates ). • Concurrent mental health and substance use disorders in general medical patients increase health care service use (Kathol et al, 2005;Thomas et al, 2005;Thomas et al, 2006). • Effectively treating mental conditions in general medical patients reverses poor health and cost outcomes Unutzer et al, 2008).…”
Section: Integrated Case Managementmentioning
confidence: 96%
“…Both of these discrete events occurred concurrent to the initial penetration of Medicaid managed care and allowed for the rapid awakening of the clinic. It was, however, the continued presence of Medicaid managed care which encouraged the clinic to remain awake 3. As the company also serves recipients of other publicly-funded programs including Medicare, it is not completely accurate to refer to the company as a Medicaid managed care company.…”
mentioning
confidence: 95%
“…There are also weekly joint rounds, joint educational activities and the co-location of all clinical staff. For more on some of the issues surrounding this Cartesian split see[2][3][4][5].…”
mentioning
confidence: 99%